Melting of SiC powders preplaced duplex stainless steel using TIG welding - Maleque, Md. Abdul; Afiq, Muhammad (IOP Publishing Ltd, 2018)
TIG torch welding technique is a conventional melting technique for the cladding of metallic materials. Duplex stainless steels (DSS) show decrease in performance under aggressive environment which may lead to unanticipated failure due to poor surface properties. In this research, surface modification is done by using TIG torch method where silicon carbide (SiC) particles are fused into DSS substrate in order to form a new intermetallic compound at the surface. The effect of particle size, feed rate of SiC preplacement, energy input and shielding gas flow rate on surface topography, microstructure, microstructure and hardness are investigated. Deepest melt pool (1.237 mm) is produced via TIG torch with highest energy input of 1080 J/mm. Observations of surface topography shows rippling marks which confirms that re-solidification process has taken place. Melt microstructure consist of dendritic and globular carbides precipitate as well as partially melted silicon carbides (SiC) particles. Micro hardness recorded at value ranging from 316 HV0.5 to 1277 HV0.5 which shows increment from base hardness of 260 HV0.5kgf. The analyzed result showed that incorporation of silicon carbide particles via TIG Torch method increase the hardness of DSS.